Experimental investigation of the influence of a reverse delta type add-on device on the flap-tip vortex of a wing - Altaf, Afaq; Thong, Tan Boon; Omar, Ashraf Ali; Asrar, Waqar (IOP Publishing, 2017)
Particle Image Velocimetry was used in a low speed wind tunnel to investigate the effect of interactions of vortices produced by an outboard flap-tip of a half wing (NACA 23012 in landing configuration) and a slender reverse delta type add-on device, placed in the proximity of the outboard flap-tip, on the upper surface of the half wing. This work investigates the characteristics of the vortex interactions generated downstream in planes perpendicular to the free stream direction at a chord-based Reynolds number of Re c =2.74×105 . It was found that the add-on device significantly reduces the tangential velocity magnitude and enlarges the vortex core of the resultant vortex by up to 36.1% and 36.8%, respectively.